2018
DOI: 10.1055/a-0586-8406
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of 5-Fluorouracil-Loaded Chitosan Microspheres for the Intranasal Administration

Abstract: The optimized technique has a good reproducibility and a high entrapment efficiency, so it could be used to prepare 5-fluorouracil-loaded chitosan microspheres for the intranasal administration.Chitosan is a good material for nasal preparation and has prospective development in the pharmaceutical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although both PTX EtOH - and PTX nano -GP-MS were able to prolong the residence time of PTX in the abdominal cavity, PTX nano -GP-MS were more efficacious in eradicating minimal peritoneal disease and preventing recurrent peritoneal carcinomatosis. It has already been reported that PTX nanocrystals demonstrate a high cellular uptake due to their size and accumulate in tumor tissue, increasing the efficacy of PTX therapy 13,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Although both PTX EtOH - and PTX nano -GP-MS were able to prolong the residence time of PTX in the abdominal cavity, PTX nano -GP-MS were more efficacious in eradicating minimal peritoneal disease and preventing recurrent peritoneal carcinomatosis. It has already been reported that PTX nanocrystals demonstrate a high cellular uptake due to their size and accumulate in tumor tissue, increasing the efficacy of PTX therapy 13,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature [ 9 , 24 , 35 ], 50 mg of aerogel was accurately weighed and placed in 50 mL HCl aqueous solution (pH = 1) and desorption of 5-Fu occurred at 60 °C for 3 h. Next, the absorbance of 1 mL of filtrate was measured at 265 nm. The drug loading (DL) and encapsulation efficiency (EE) were calculated using the following equation: DL = [Drug loading/(Drug loading + Aerogel)] × 100% EE = (Determined drug loading/(Theoretic drug loading) × 100% …”
Section: Methodsmentioning
confidence: 99%
“…In recent times, microsphere formulations have achieved tremendous significance as oral drug delivery systems due to predictable gastric emptying, reduced local irritation and fewer toxic effects as compared to unit dosage forms which make these systems more preferable. Chitosan has been used as an ex-cipient of choice in formulating biodegradable microspheres owing to its property of modifying the drug release and also exerting mucoadhesive effect [1][2][3]. Since the matrices made of cross-linked chitosan amicably alter the release of a loaded drug, so the current study endeavored the determination of effect of diverse cross-linking agents on the release of drug loaded in chitosan microspheres.…”
Section: Introductionmentioning
confidence: 99%